2020
DOI: 10.1016/j.tra.2020.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Does free-floating carsharing reduce private vehicle ownership? The case of SHARE NOW in European cities

Abstract: Highlights Survey of free-floating carsharing users carried out in 11 European cities. Each SHARE NOW car replaces up to 20 private cars. The probability of selling private cars increases with kilometres by this service. City-specific characteristics affect private car sales. The car fleet was reduced due to free-floating carsharing in all cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 34 publications
1
33
1
Order By: Relevance
“…A fictitious advertisement based on a picture from the website Wikipedia Commons ( 2014 ) promoting a well-known carsharing service—ShareNow, the world's largest provider of free-floating carsharing—was used as stimulus material. ShareNow (and car2go and DriveNow, the precursory organizations before their merger in 2019) have been frequently investigated in prior studies (e.g., Firnkorn, 2012 ; Kortum et al, 2016 ; Jochem et al, 2020 ). Our stimulus focused on the German market, which is ShareNow's largest one (ShareNow, 2020b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A fictitious advertisement based on a picture from the website Wikipedia Commons ( 2014 ) promoting a well-known carsharing service—ShareNow, the world's largest provider of free-floating carsharing—was used as stimulus material. ShareNow (and car2go and DriveNow, the precursory organizations before their merger in 2019) have been frequently investigated in prior studies (e.g., Firnkorn, 2012 ; Kortum et al, 2016 ; Jochem et al, 2020 ). Our stimulus focused on the German market, which is ShareNow's largest one (ShareNow, 2020b ).…”
Section: Methodsmentioning
confidence: 99%
“…Münzel et al, 2019 ). Jochem et al's ( 2020 ) survey-based study on the impact of carsharing on private car ownership across 11 European cities revealed that one free-floating carsharing service replaces at least eight private cars and, in optimistic scenarios, even up to 20 cars. In this context, shared mobility services in general and free-floating carsharing in specific can mitigate public costs associated with personal car use and help cities in their development of a sustainable transportation strategy (Terrien et al, 2016 ; Shaheen et al, 2020 ).…”
Section: Conceptual Research Frameworkmentioning
confidence: 99%
“…But so far, public transportation has been less popular with Russian residents than personal transportation, according to a report on the implementation of the current transportation strategy, which was adopted in 2013. In 2019, the tendency of passengers leaving public transport continued, «despite the growing attractiveness of urban passenger transport systems and cab and carsharing services» [1][2][3][4], due to dramatically improved road conditions, especially in the European part of the country, which allowed the use of personal cars, both for business trips and for tourism.…”
Section: Introductionmentioning
confidence: 99%
“…The sharing economy seeks a more efficient use of resources with positive economic, social and environmental consequences [1]. Abandoning possession in favour of temporary access to a good or service makes the system more economically and environmentally efficient [2].…”
Section: Introductionmentioning
confidence: 99%